Digital electronics: principles and practice - Kapoor, Avinashi; Maheshwari, L.K. (Delhi : MacMillan India Ltd., 2004)
Engineering
Keywords: Digital electronics; Binary logic; Combinational circuits; Sequential logic; Logic circuits; Digital electronics; Digital circuits; Arithmetic circuits